Activity Therapy Group Gymnastics for Elderly Patients with Diabetus Militus in Karangmangu Village, Kroya Cilacap District: Terapi Aktifitas Kelompok Senam Lansia Penderita Diabetus Militus di Desa Karangmangu Kecamatan Kroya Cilacap - Marsito, M; Saraswati, Rina; Ernawati, E; Sutanto, Eko; Jatmiko, Danang (Prosiding University Research Colloquium, 2023)
DM cases in Central Java reached 13.4% in 2019, while the elderly in Cilacap Regency reached 61,713 people. Service achievement in Cilacap district is still 17.3% less than 100%. Therefore, it is necessary to carry out community service activities through empowerment with a group activity therapy model. The participants were the elderly of Karangmangu Village, Kroya Cilacap, totaling 15 people who experienced diabetes militus complaints. the purpose of this service is to reach the service coverage of DM sufferers. The method in implementing community service uses empowerment through group activity therapy. All of these implementations can be useful for increasing the coverage of DM health services. The results of community service activities through screening and TAK found that the majority of 15 elderly people who experienced high blood sugar at any time there were 9 people (60%), increased blood pressure there were 11 people (73.3%) out of 15 people. The implementation of community service through empowerment of DM sufferers with a group activity therapy model doing sports exercises can be applied.